Contemporary biophysical approaches for studying 14-3-3 protein-protein interactions - Thurairajah, Bethany; Hudson, Andrew J.; Doveston, Richard G. (Frontiers in Molecular Biosciences, 2022)
14-3-3 proteins are a family of regulatory hubs that function through a vast network of protein-protein interactions. Their dysfunction or dysregulation is implicated in a wide range of diseases, and thus they are attractive drug targets, especially for molecular glues that promote protein-protein interactions for therapeutic intervention. However, an incomplete understanding of the molecular mechanisms that underpin 14-3-3 function hampers progress in drug design and development. Biophysical methodologies are an essential element of the 14-3-3 analytical toolbox, but in many cases have not been fully exploited. Here, we present a contemporary review of the predominant biophysical techniques used to study 14-3-3 protein-protein interactions, with a focus on examples that address key questions and challenges in the 14-3-3 field.